Hydrogen vehicles in urban logistics: A total cost of ownership analysis and some policy implications. (March 2020) - Jones, J.; Genovese, A.; Tob-Ogu, A.
Abstract: Freight transport accounts for 8–15% of total traffic flow in urban areas within the European Union. The majority of these deliveries are undertaken by diesel-powered vehicles with extremely disproportionate levels of CO2, NOx and particulate matter emissions. Accordingly, a variety of strategic options have been advanced as key solutions for addressing fossil fuel demand and emissions in urban freight transport. This paper progresses the discourse on hydrogen vehicles as viable strategic options for addressing sustainability concerns in urban logistics by undertaking a comprehensive total cost of ownership analysis. Outcomes from this study not only support the economic competitiveness of hydrogen vehicles, but also analyse implications of several future policy and market scenarios. Highlights: A TCO approach is proposed for evaluating the potential of hydrogen vehicles in urban logistics. An extensive sensitivity analysis is performed. Policy recommendations are provided.